PERMUKIMAN KUMUH, SEBUAH KEGAGALAN PEMENUHAN ASPEK PERMUKIMAN ISLAMI - Handryant, Aisyah Nur (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2011)
As a social being, interaction with others is one of human’s essential needs. These interaction and socialization in a society is often conducted in a settlement. A settlement as a community ecosystem has an important role in shaping people’s characters in a society. The condition of settlement can be an indication of the condition of its community. On the other hand, Islam as a rahmatan lil 'alamin religion actually provides its followers a set of values on islamic aspects in the house and settlement. Islam gives some lessons of how a house could become not only as a gathering place for family members, but could also be a place of education and learning for its inhabitants. Islam also gives us lessons of how a house is closely related to its settlement and environment, and how every elements in a house should be in harmony and unity with its social and natural environment. This paper tries to analyze many aspects of slums based on some aspects of islamic housing. The deficiencies and problems found in slums are expected as a consideration in the future efforts to overcome the problems holistically and integrally. Keywords: Slum, islamic settlement, house